Cost of renal replacement therapy in Turkey - (:unkn) unknown (BLACKWELL PUBLISHING ASIA, 2004)
Background and Resluts: By the end 2000, 22 224 patients were on renal replacement therapy (RRT) in Turkey. We investigated the cost of RRT in three medical faculties and one private dialysis centre. Yearly expenses were US$22 759 for haemodialysis (HD), US$22 350 for continuous ambulatory peritoneal dialysis (CAPD), and US$23 393 and US$10 028, respectively, for the first and second years of transplantation (Tx). In the first year, renal Tx was significantly more expensive than CAPD. However, after the first year of renal transplantation, Tx became significantly more economical than both CAPD and HD. The sum of all yearly RRT expenses for the country was US$488 958 709, which corresponds to nearly 5.5% of Turkey's total health expenditure. Conclusion: Measures such as early construction of vascular access, promoting home dialysis and the reuse of the dialysers, strict control of the use of some expensive drugs like erythropoietin and active vitamin D, and also increasing the number of transplantations, especially if pre-emptive transplantation is possible, should be taken into account in order to reduce these expenses.
Keywords: cost; dialysis; transplantation; DIALYSIS; DISEASE